Acute respiratory distress syndrome due to clostridium difficile after total pancreatectomy (Revista Argentina de Cirugía, 2021)
Nosocomial (hospital-acquired) diarrhea is usually caused by Clostridium difficile. On rare occasions it can cause acute respiratory distress syndrome (ARDS). Therefore, this condition should be suspected in order to make a diagnosis. Treatment is based on oral antibiotics. We report the case of a 66-yearold female patient with ARDS secondary to Clostridium difficile colitis after total pancreatectomy.
Keywords: Pancreatectomy; distress; Clostridium